UPAYA MENINGKATKAN HASIL BELAJAR SISWA DENGAN MENGGUNAKAN METODE MIND MAPPING PADA MATA PELAJARAN PKN DI KELAS V SD NEGERI 2 SOKO KECAMATAN TIKUNG KABUPATEN LAMONGAN - Ruslan Ruslan (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2022)
The aims of the study: (1) To find out how students' learning outcomes in Civics subjects were before using the Mind Mapping method (2) To find out how the Mind Mapping method was applied (3) To find out how students responded after applying the Mind Mapping method. Based on the results of the study it can be concluded that: (1) Student learning outcomes before using the Mind Mapping method, namely 4 students who complete or with a percentage of 33.3%. (2) The ability of students after using the Mind Mapping method, namely in the first cycle, there were 7 students who completed or with a percentage of 58.3%. Furthermore, in cycle II, 11 students who completed it or with a percentage of 91.2%. This shows that the ability of students in learning has reached a mastery level of classical learning of 75%. (3) Student responses using the Mind Mapping method in Civics learning were positive. Thus, it can be concluded that using the Mind Mapping method can improve students' abilities in learning Civics.